Improving Students’ Achievement in Reading Comprehension Through Advance Organizer Strategy - Tuti Andriani Siregar; Didik Santoso; Anni Holila Pulungan (Universitas Negeri Medan, 2015)
This study deals with the improvement of the students’ achievement in reading comprehension through advance organizer strategy. The objectives of this research were to improve the students’ achievement in reading comprehension as well as the process of learning reading comprehension by using advance organizer strategy. The subject of the study was grade XI IPA 2 Madrasah Aliyah Negeri Binjai consisting of 33 students. The data of this study were obtained by using test, observation sheets and interview. This research was conducted in two cycles because in the pre-test (without treatment), the average of the students’ score was 59,24. In the first cycle test, it was 74,30. It is lower than the minimum passing grade, and if is viewed from the observation sheets, the situation of the learning process hasn’t met the criteria of the success. So the writer continued to the second cycle. There was a significant progress on the students’ achievement in reading comprehension in the second cycle, and the average of the students was 82,94. The students were more active and enthusiastic in following the lesson. Therefore, the teaching reading comprehension through advance organizer strategy can improve the students’ achievement in reading comprehension quantitatively and qualitatively. Key words: improving, reading comprehension, advance organizer strategy.